The Dominance Pattern of Coronary Artery of Adult Bangladeshi People- A Postmortem Morphological Study - Hussain, MA; Nahar, A; Ara, S (Cardiovascular Journal, 2011)
Background: Incidence of the heart disease increases day by day in Bangladesh. Recent advances in cardiac surgery and the search for new techniques toward investigation of the heart are demanding a review of the anatomy of the coronary arteries. Method: The present study was performed on sixty (60) adult postmortem human hearts of Bangladeshi people. The samples were divided into 3 age groups: Group A (20 to 40 years) consists of 35 male & 7 female samples, Group B (41 to 60 years) consists of 3 female samples and Group C (61 to 75 years) consists of 7 male samples. Results: In the present study, dominance pattern of the coronary artery was right for male in-group A, B, C were 32 (91.4%), 7(87.5%), 6(85.7%), respectively and for female were 6 (85.7%). 3 (100%) respectively. It was left for male in-group A, B, C were 3 (8.6%), 1 (12.5%), 1(14.3%), respectively and for female was 1 (14.3%). Conclusion: The results of the present study can be helpful to the cardiologists and cardiovascular surgeons in the proper diagnosis and management of the heart diseases. Key words : Postmortem heart, Coronary arteries, Ischaemic heart disease. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8200 Cardiovasc. j. 2008; 1(1) : 21-25